2009
DOI: 10.1148/radiol.2532090200
|View full text |Cite|
|
Sign up to set email alerts
|

Recommendations for Additional Imaging in Radiology Reports: Multifactorial Analysis of 5.9 Million Examinations

Abstract: The likelihood of RAI increased by 15% for each decade of radiologist experience and roughly doubled over 13 years of study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 17 publications
6
66
6
Order By: Relevance
“…A prior study found that the overall rate of recommending additional imaging decreased as radiologists' experience increased. 8 However, we did not observe this trend. In fact, the more experienced radiologists were most likely to report ITNs in the "Impression" section and recommend work-up, and radiologists with 5-9 years' experience were least likely to report ITNs in the "Impression" and recommend work-up.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…A prior study found that the overall rate of recommending additional imaging decreased as radiologists' experience increased. 8 However, we did not observe this trend. In fact, the more experienced radiologists were most likely to report ITNs in the "Impression" section and recommend work-up, and radiologists with 5-9 years' experience were least likely to report ITNs in the "Impression" and recommend work-up.…”
Section: Discussioncontrasting
confidence: 68%
“…Different recommendations for patients with the same nodule characteristics and clinical history are problematic because they can lead to variation in practice patterns, potential variation in the quality of patient care, and anxiety for patients, and they can po-tentially increase health care costs from the performance of more imaging studies, biopsies, and diagnostic surgeries. 2,[7][8][9] Although some incidental cancers may be diagnosed and treated at an earlier stage, Ͼ50% of patients with ITNs that have surgery will ultimately be diagnosed with benign disease. 10,11 The variation in reporting styles for ITNs seen on CT and MR imaging has been measured in a recent study, which surveyed radiologists on how they reported different scenarios varying in nodule size and patient history.…”
mentioning
confidence: 99%
“…(Fig 10 reprinted, with permission, from reference 9.) partment (44). In addition to observing a doubling of the proportion of examinations that contained at least one recommendation for additional imaging during the study period (from 6% to 12%), the authors assessed correlations with imaging modality, body area examined, ordering service, and radiologist specialty (44).…”
Section: Recommendation Practices and Communication Of Critical Resultsmentioning
confidence: 99%
“…partment (44). In addition to observing a doubling of the proportion of examinations that contained at least one recommendation for additional imaging during the study period (from 6% to 12%), the authors assessed correlations with imaging modality, body area examined, ordering service, and radiologist specialty (44). Such information can be used for quality improvement, performance quantification, and (potentially) feedback for individual radiologists on their recommendation rates.…”
Section: Recommendation Practices and Communication Of Critical Resultsmentioning
confidence: 99%
“…Follow-up recommendations in radiology reports are both common and increasingly utilized [2]. But what is the fundamental role of the recommendation?…”
mentioning
confidence: 99%